Analisis Yuridis Kekuatan Pembuktian Visum Et Repertum dalam Tindak Pidana Penganiayaan: Studi Putusan Perkara Nomor 78/Pid.B/2023/PN.Bta - Hidayah, Hasmi Kun; Prawitasari, Nining Yurista (Universitas Islam Negeri Alauddin Makassar, 2024)
Visum Et Repertum is a valid evidence tool that has a very important role and power in the trial of criminal cases, especially in criminal cases where the object is the human body, in addition to simplifying the evidentiary process, it can also convince the judge in deciding a case. This research method uses normative juridical research approaches, legislation, conceptual approaches, and case approaches. The results of the study show that the judge in deciding the case went through several considerations, namely considerations with several pieces of evidence submitted by the public prosecutor as well as incriminating considerations and mitigating considerations for the defendant. In the verdict, the Defendant SA als Aan Bin RC was found guilty of his actions, namely deliberately persecuting the witness MA Bin MY. The defendant received a sanction, namely imprisonment for 2 (two) years and 3 (three) months.